The electronic transport properties [Co2(L)L?(dioxane)2(NO3)2](NO3)2 of the complex - Yakuphanoğlu, Fahrettin; Aydogdu, Y; Gömleksiz, M; Sekerci, M; Agan, S; Alkan, C (Elsevier, 2003)
The temperature dependence of the electrical conductivity, microstructure and crystal structure properties of the [Co,(L)L'(dioxane)(2)(NO3)(2)](NO3)(2) complex was investigated. The X-ray diffraction showed that the [Co,(L)L'(dioxane)(2) (NO3)(2)](NO3)(2) has a triclinic structure. Temperature dependence of the conductivity curve of the complex exhibited two conduction regions, and while increase of conductivity with temperature in the first region is of hopping conduction which takes place in localized states, the conduction in the second region is of Arrhenius-type. These conduction mechanisms are related to intermolecular and intramolecular conduction progresses. The electrical conductivity of the [Co-2(L)L'(dioxane)(2)(NO3)(2)](NO3)(2) complex was 2.57 x 10(-7) (S/cm) at room temperature with activation energy of 0.46 eV which showed semiconductivity behavior. (C) 2002 Published by Elsevier Science B.V.
Keywords: complex; semiconductor; electrical conductivity